Selective survey on Subset Combinatorics of Groups - Protasov, I.V. (Український математичний вісник, 2010)
We survey recent results concerning the combinatorial size of subsets of groups. For a cardinal k, according to its arrangement in a group G, a subset of G is distinguished as k-large, k-small, k-thin, k-thick and Pk-small. By analogy with topology, there arise the following combinatorial cardinal invariants of a group: density, cellularity, resolvability, spread etc. The paper consists of 7 sections: Ballean context, Amenability, Ideals, Partitions, Packings, Around thin subsets, Colorings.